Contemporary Myths, Sexuality Misconceptions, Information Sources, and Risk Perceptions of Bodabodamen in Southwest Uganda - Nyanzi, Stella; Nyanzi, Barbara; Kalina, Bessie (Sex Roles, 2005)
This article reports findings from a study conducted among 212 private motorbike–taxi riders, locally called bodabodamen, from two study sites—a slum area and the urban center of Masaka town. Qualitative and quantitative methods were triangulated; a questionnaire, focus group discussions, in-depth interviews, case studies, and interactive workshops were all used. There were high levels of awareness of HIV, much more than sexually transmitted diseases (STDs), because many participants had closely experienced HIV/AIDS. Knowledge about sexual health contained several misconceptions, misinformation, and myths rooted in both the historical and contemporary social cultural context. Due to high illiteracy levels, bodabodamen cannot access many standard health education materials issued by government and private health organizations through the print and electronic media, as well as those published in languages other than the local vernacular. These (and possibly other) disadvantaged groups remain at risk of HIV and STDs. Especial efforts need to be made to provide appropriate health education.
Keywords: sexuality information; risk perceptions; masculinity.